Analisis Perbandingan Investasi Sukuk Tabungan dan Sukuk Ritel: Pendekatan terhadap Karakteristik, Kinerja Historis, Risiko, dan Dampak Ekonomi - Franky Napitupulu; Kartika Wijaya; Wisudanto Mas Soeroto (Journal on Education, 2024)
This research aims to compare investments between Sukuk Tabungan and Sukuk Ritel by discussing relevant aspects. The focus of analysis covers the purpose of issuance, structural characteristics, historical performance, risk, investor preferences, regulations, and their impact on the economy. In this research, analysis is conducted through two approaches: descriptive comparison and historical analysis. Descriptive comparison refers to the direct comparison of the characteristics of Sukuk Tabungan and Sukuk Ritel, while historical analysis is based on relevant historical data. Additionally, there will be an additional analysis of external factors such as macroeconomic conditions on the performance and risk of Sukuk Tabungan and Sukuk Ritel. It is expected that the results of this research will provide a deeper understanding for investors, regulators, and other related parties about the implications of choosing between Sukuk Tabungan and Sukuk Ritel in managing their investment portfolios more effectively.